Lactate Is a Metabolic Mediator That Shapes Immune Cell Fate and Function - Caslin, Heather L.; Abebayehu, Daniel; Pinette, Julia A.; Ryan, John J. (Frontiers in Physiology, 2021)
Lactate and the associated H+ ions are still introduced in many biochemistry and general biology textbooks and courses as a metabolic by-product within fast or oxygen-independent glycolysis. However, the role of lactate as a fuel source has been well appreciated in the field of physiology, and the role of lactate as a metabolic feedback regulator and distinct signaling molecule is beginning to gain traction in the field of immunology. We now know that while lactate and the associated H+ ions are generally immunosuppressive negative regulators, there are cell, receptor, mediator, and microenvironment specific effects that augment T helper (Th)17, macrophage (M)2, tumor associated macrophage, and neutrophil functions. Moreover, we are beginning to uncover how lactate and H+ utilize different transporters and signaling cascades in various immune cell types. These immunomodulatory effects may have a substantial impact in cancer, sepsis, autoimmunity, wound healing, and other immunomodulatory conditions with elevated lactate levels. In this article, we summarize the known effects of lactate and H+ on immune cells to hypothesize potential explanations for the divergent inflammatory vs anti-inflammatory effects.